Different stones: the weight of colour in ancient near Eastern glyptic - Di Ludovico, Alessandro (2025)
The cylinder seals of ancient Western Asia are a category of artefacts with a wide range of characteristics and implications. Their use was both administrative and bureaucratic, but they were ornamental and apotropaic objects too, thus acquiring diverse symbolic and cultural values. Moreover, they were mostly experienced by their owners and users by being kept in close contact with their bodies. This means that the physical characteristics of the seals (colour, conductivity, weight, etc.) probably had some importance for the ancient societies using them. Thanks to widespread and precise digital technologies, the recording of the data of seals has grown significantly in recent years. In this preliminary work, primary and secondary visual data and the metadata thus obtained have been collected, and statistical analyses have been carried out with the objective of testing the possibility of mapping the general colour trends of ancient Near Eastern glyptics.